CHALLENGES IN NURSING CARE FOR THE TRANSEXUAL POPULATION IN PRIMARY HEALTHCARE: AN INTEGRATIVE REVIEW - Lima, Pedro (2025)
The objective of this article is to discuss the main perspectives regarding nursing careprovided to the transgender population in health services. This is an integrative literaturereview conducted in the BDENF database, using the descriptors "Transsexuals," "HealthCare," and "Nursing Care," combined with the boolean operator AND. Articles publishedbetween 2018 and 2024, in Portuguese, English, and Spanish, and available in full text wereincluded. After applying the exclusion criteria, 10 articles were selected and grouped intothree categories. The first category addresses the low attendance of the transgenderpopulation in health services and their limited adherence to the offered actions. The secondhighlights the importance of the visibility of the transgender community within hospitalsettings. The last category deals with the deep-rooted prejudice among healthcareprofessionals toward this population, which unfortunately hinders the guarantee of theirhealth rights. From the analysis of the selected literature, it was possible to infer that thetransgender population faces several issues concerning access to primary health care. Thisstudy will discuss aspects ranging from their invisibility to the care provided in hospitalsettings.